Analysis of the key ligand receptor CADM1_CADM1 in the regulation of thyroid cancer based on scRNA-seq and bulk RNA-seq data - He, Hui; Cong, Shan; Wang, Yu; Ji, Qinghai; Liu, Weiyan; Qu, Ning (Frontiers in Endocrinology, 2022)
Advanced papillary thyroid cancer (PTC) has a poor prognosis, 60~70% of which become radio iodine refractory (RAI-R), but the molecular markers that assess PTC progress to advanced PTC remain unclear. Meanwhile, current targeted therapies are badly effective due to drug resistance and adverse side effects. Ligand-receptor pairs (L/R pairs) play an important role in the interactions between tumor cells and other cells in the tumor microenvironment (TME). Nowadays, therapies targeting ligand-receptor pairs in the TME are advancing rapidly in the treatment of advanced cancers. However, therapies targeting L/R pairs applied to advanced PTC remains challenging because of limited knowledge about L/R pairs in PTC. Here, we screened the critical L/R pair: CADM1-CADM1 using 65311 single-cell RNA sequencing (scRNA-seq) samples from 7 patients in different stage of PTC and bulk RNA-seq datasets containing data from 487 tumor samples and 58 para-carcinoma samples. We found that CADM1_CADM1 could be regarded as a biomarker representing a good prognosis of PTC. In addition, the high expression of CADM1_CADM1 can strongly increase the sensitivity of many targeted drugs, which can alleviate drug resistance. We further discussed the biological processes and pathways associated with CADM1_CADM1. Taken together, our study identified that CADM1_CADM1 played an essential role in the progression of PTC for the first time and our findings provide a new potential prognostic and therapeutic ligand-receptor pair for advanced PTC.